The design and characterization of breakdown mechanism on p+/n- well single photon Avalanche Diode (Spad) - Wong, Cindy E. Lin (2015)
In this paper, the breakdown voltage (VBD) and dark current (ID) of p+/n-well avalanche photodiodes operating in Geiger is reported. Simulations are performed by implemented the numerical simulations at the technological process and electrical level by using two dimensional TCAD simulations. The simulation analysis aims at relating both the VBD and ID to the relevant the device parameters, such as epitaxial layer thickness and doping concentration, in the context of device performance optimization for photon counting application. The optimized design of the Single Photon Avalanche Diode (SPAD) is included with the guard ring by the diffusion of p-wells layer to prevent the edge breakdown by limiting the high electric field at the junction periphery of the device. The result demonstrated that, the SPAD with square shape active area of 2 x 2 µm2 using low doped p-well guard ring has VBD of 27 V and IA of 0.85 pA. The simulation performances are also useful for characterization performance of silicon SPAD prior fabrication in low voltage CMOS Process.